Mechanistic studies on a Cu-catalyzed asymmetric allylic al-kylation with cyclic racemic starting materials - Rideau, E; You, H; Sidera, M; Claridge, T; Fletcher, S (American Chemical Society, 2017)
Mechanistic studies on Cu-catalysed asymmetric additions of alkylzirconocene nucleophiles to racemic allylic halide electrophiles were conducted using a combination of isotopic labelling, NMR spectroscopy, kinetic modeling, structure-activity relationships and new reaction development. Kinetic and dynamic NMR spectroscopic studies provided insight into the oligomeric Cu-ligand complexes, which evolve during the course of the reaction to become faster and more highly enantioselective. The Cu-counterions play a role in both selecting different pathways and in racemizing the starting material via formation of an allyl iodide intermediate. We quantify the rate of Cu-catalyzed allyl iodide isomerization and identify a series of conditions under which the formation and racemization of the allyl iodide occurs. We developed reaction conditions where racemic allylic phosphates are suitable substrates using new phosphoramidite ligand D. D also allows highly enantioselective addition to racemic 7-membered-ring allyl chlorides for the first time. 1H and 2H NMR spectroscopy experiments on reactions using allylic phosphates showed the importance of allyl chloride intermediates, which form either by the action of TMSCl or from an adventitious chloride source. Overall these studies support a mechanism where complex oligomeric catalysts both racemize the starting material and select one enantiomer for a highly enantioselective reaction. It is anticipated that this work will enable extension of copper-catalyzed asymmetric reactions and provide understanding on how to develop dynamic kinetic asymmetric transformations more broadly.